Evaluation on material and heat balance of EAF processes with introduction of CO2 - Wang H.; Yu H.; Teng L.; Seetharaman S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The advantages of using CO2 for the decarburization of high alloy steels have been recognized from environmental and economic view points. The present paper presents the heat and materials balances in the decarburization process with the introduction of CO2 as a diluting gas in Electric Arc Furnace (EAF) process for steel production. The aim is to optimize the amount of CO2 and the materials requirements, which includes the addition of scrap, hot metal and coolant. These estimations are also important to control the bath temperature, thereby prolong the lifetime of the refractory lining of the furnace. The present calculations enable an optimization of the CO2:O2 ratio and materials input in the decarburization of carbon steel melts. Another important extension of the work is the possibility to enhance the addition of hot metal during steel making process. The present results show that addition of up to 20% hot metal is likely to the energy loss due to the introduction of 50% CO2 for a 110 tons EAF resulting in the saving of electric energy.